Titanium Dioxide Mediated Photocatalytic Degradation of Chlorpyrifos in Aqueous Phase - Yadav, Poonam (My University, 2010)
Pesticides are widely utilized at various stages of cultivation and during postharvest storage to protect plants against a range of pests and /or to provide quality preservation & for the preparation of pesticide most hazardous organic and inorganic chemical are used. In developing countries, pesticides use are growing, its excessive and inadequate use leads the pollution i.e. pesticide pollution. This organic pollutant cannot be completely degraded by conventional techniques like adsorption, coagulation and flocculation, precipitation, biological treatment etc. The incapability of conventional wastewater treatment methods to remove effectively such pollutant lead to explore new ,efficient and cost effective treatment systems. In order to meet the environment standards, the latest technologies are required to mineralize these bio-recalcitrant organic compounds. Photocatalysis provides a new method for water decontamination. Recent intensive study showed that it can be applied to the degradation of many pollutants. Among them, pesticides have been considered to be one of the major pollutants to which it is promising to apply photocatalysis. The use of high energy oxidants produces hydroxyl radical (OH) and these radicals have high oxidizing power superior to other usual oxidants and helps in complete degradation of complex organic compound into CO2 and H2O.This methods are called advanced oxidation processes ( AOPS), which results in formation of hydroxyl radical (OH) as a primary oxidant. The advanced oxidation process uses the H2O2/ UV, O3/H202, UV/O3, and others techniques are sonolysis (ultrasonic irradiation, sonophotocatalysis etc. In the project the technical grade pesticide Chlorpyrifos degradation was studied. Titanium Dioxide (TiO2) is used as a Photocatalyst. The main aim of the process is to degrade the toxic complex structure of the technical grade chlorpyrifos pesticide to harmless product by treating the sample in the UV-reactor by varying pH, catalyst concentration, oxidant (H2O2). Degradation was followed by measuring the chemical oxygen demand (COD). The scope of this project is to see advanced oxidation process as a viable treatment option in case of pesticides. Experiment was performed in both UV and solar light at optimized condition. The degradation of pesticide has been investigated in terms of reduction in COD. Various parameters like catalyst dose, pH, and oxidant dose these concentration and effects has been analysed. In this case catalyst concentration was optimized at 0.8 g/200 ml, pH 6.5 and oxidant concentration at 2 ml/200ml sample. V The results obtained were quit appreciable as it reduced COD from 12800 mg/L to 1800 mg/L. The results of photocatalysis got better by the introduction of high power ultrasound (i.e., sound energy with frequencies in the range of 15 kHz to ~1MHz) for the uniform distribution of the catalyst slurry. The maximum degradation of chlorpyrifos pesticide showed photocatalysis would be used as efficient and environment friendly technique for the complete degradation of toxic organic pollutants which will increase the chances of getting rid of these type of chemicals from water/wastewater. The investigations demonstrate the importance of selecting the optimal degradation parameters for practical applications of this operation.
M.Tech. (Environmental Science and Technology)
Keywords: Photocatalytic Degradation; Aqueous Phase